A REVISION OF THE GENUS SPATHOLOBUS (LEGUMINOSAE-PAPILIONOIDEAE) - Jeannette W. A; Ridder-Numan; Harry Wiriadinata (Reinwardtia, 1984)
In the S. E. Asiatic genus Spatholobus 28 species are recognized, 6 of which are never described before: S. albus S. auricomus, S. auritus, S. hirsutus, S. multiflorus and S. viridis. One variety (S. ferrugineus var. acutus) is also newly described. A key and full descriptions with plates and maps to illustrate the distribution are given.